Hari tanpa Daging: Studi Pasca Kolonial tentang Identitas, Migrasi, dan Kenangan yang Tumpang Tindih - Shahzaib Hassan (FOCUS, 2022)
This research paper aims to critically analyze the political, lingual and religious identity crises of the people of the third world. For that purpose, the primary text selected is Meatless Days written by Sara Suleri. The theoretical framework employed to provide character analysis is post-colonialism of Edward Said and Gayatri Spivak. Throughout this research, the concept of “the orient" and "the occident" (Selden et al. 220) given by Said is invoked in addition to the concept of “anomaly” given by Spivak. Firstly, the primary resource is analyzed from the theoretical lens of Said and Spivak in order to provide a wider commentary on the political, lingual and religious identities of the people of the third world. Secondly, this research divests the myths, established by the Western philosophers regarding "the orient" (people of the Global South/East or third world) as irrationally religious, apolitical and amoral, through the primary resource. Lastly, this research paper establishes a case for fluidity of identities, of characters presented in Meatless Days, as a result of dislocation and migration.